2015
DOI: 10.1016/j.biortech.2015.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion of paper mill sludge to bioethanol in the presence of accelerants or hydrogen peroxide pretreatment

Abstract: In this study we investigated the technical feasibility of convert paper mill sludge into fuel ethanol. This involved the removal of mineral fillers by using either chemical pretreatment or mechanical fractionation to determine their effects on cellulose hydrolysis and fermentation to ethanol. In addition, we studied the effect of cationic polyelectrolyte (as accelerant) addition and hydrogen peroxide pretreatment on enzymatic hydrolysis and fermentation. We present results showing that removing the fillers co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 30 publications
(27 reference statements)
2
46
0
2
Order By: Relevance
“…To make cellulosic ethanol feasible in the market, ethanol production must be at least 76.5 g/L, which requires an initial sugar concentration higher than 150 g/L (Gurram et al 2015). In this experiment, pulp concentrations of 10%, 15%, and 20% were compared; sugar production increased Hu et al (2016).…”
Section: Effects Of Pulp Concentration On Enzymatic Hydrolysismentioning
confidence: 96%
“…To make cellulosic ethanol feasible in the market, ethanol production must be at least 76.5 g/L, which requires an initial sugar concentration higher than 150 g/L (Gurram et al 2015). In this experiment, pulp concentrations of 10%, 15%, and 20% were compared; sugar production increased Hu et al (2016).…”
Section: Effects Of Pulp Concentration On Enzymatic Hydrolysismentioning
confidence: 96%
“…CaCO 3 increases pH value of primary sludge (8-10), which is higher than the optimum pH for cellulase activity ($5). Acid pretreatments have been used, in SHF and SSF processes, to neutralize CaCO 3 (Fan and Lynd, 2007;Marques et al, 2008;Li et al, 2009;Kang et al, 2010;Wang et al, 2011;Mendes et al, 2014;Gurram et al, 2015). However, the chemical pretreatment with acids releases CO 2 , an environmental inconvenience in the process.…”
Section: Introductionmentioning
confidence: 99%
“…The major challenge of using PPMS for bioethanol production is the high content in ash, namely CaCO 3 , which adsorbs to the enzymes and increases de pH of the sludge, hindering enzymatic hydrolysis. In order to surpass this limitation, acidic treatments are frequently used to neutralize CaCO 3 [161,[167][168][169]. Moreover, the high ash content limits solid loading, leading to bigger reaction vessels, and, consequently, to increased costs.…”
Section: Bioethanol Productionmentioning
confidence: 99%
“…Also, the sludge with higher ash content led to better fermentation results [170]. Gurram et al (2015) tested chemical, with HCl, and mechanical de-ashing of primary sludge, and found that the enzymatic hydrolysis performance improved in de-ashed sludges. The authors also investigated batch SHF of different primary sludges, either chemically de-ashed or without de-ashing, when two different accelerants or H 2 O 2 pretreatment were applied to enzymatic hydrolysis.…”
Section: Type Of Ppms Fermentationmentioning
confidence: 99%